Domain optimization problems for parabolic control systems - El Yacoubi, Samira; Sokołowski, Jan (Zielona Góra: Uniwersytet Zielonogórski)
In the paper, a class of shape optimization problems associated with the optimal location of distributed controls for parabolic systems is considered. The existence of solutions to optimization problems is established using a regularization technique. The first-order optimality conditions are obtained by an application of the material-derivative method. A relaxation method is proposed and the resulting parametric optimization problems are analysed.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka